2004
DOI: 10.1038/ni1052
|View full text |Cite
|
Sign up to set email alerts
|

The STAT3 isoforms α and β have unique and specific functions

Abstract: Signal transducer and activator of transcription 3 (STAT3) is the main mediator of interleukin 6 (IL-6)-type cytokine signaling. It exists in two isoforms: the full-length STAT3 alpha and the truncated STAT3 beta, generally thought to act as a dominant negative factor. To assess their relative functions, we ablated the expression of either isoform by gene targeting. We show here that in vivo STAT3 beta is not a dominant negative factor. Its expression can rescue the embryonic lethality of a STAT3-null mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
236
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(250 citation statements)
references
References 42 publications
9
236
4
1
Order By: Relevance
“…The role of Stat3 in IL-10 gene expression was, however, confirmed in other cell lines and in knock-out mice (Herbeuval et al, 2004) (Cheng et al, 2003) (Maritano et al, 2004). Recently it was shown that SOCS3 deficiency in murine TCR-stimulated T cells led to increased Stat3 activity and IL-10 expression (Kinjyo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The role of Stat3 in IL-10 gene expression was, however, confirmed in other cell lines and in knock-out mice (Herbeuval et al, 2004) (Cheng et al, 2003) (Maritano et al, 2004). Recently it was shown that SOCS3 deficiency in murine TCR-stimulated T cells led to increased Stat3 activity and IL-10 expression (Kinjyo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although STAT3␤ was originally considered to be a negative regulator of transcription (16), it was later shown that the STAT3 isoforms ␣ and ␤ have unique and specific functions (18). Both seem to be necessary for the correct balance of immune responses, because the specific ablation of STAT3␤ impairs recovery from endotoxin shock and affects STAT3-dependent gene expression (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from liver samples, and 20 g of RNA was converted to cDNA with StrataScript reverse transcriptase (FairPlay Microarray Labeling Kit; Stratagene), using oligo(dT) [12][13][14][15][16][17][18] as a primer. cDNA was purified and labeled with Cy3 and Cy5 (Amersham Biosciences).…”
Section: Mouse High-density Oligonucleotide Microarraysmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice exhibited an altered pattern of STAT3-responsive gene expression, suggesting a role for the STAT3β isoform in controlling systemic inflammation [12]. Similarly, other work has argued that the STAT3β isoform is not a true dominant-negative factor, as it retains the ability to activate a number of STAT3 target genes [13]. The STAT4β isoform has also been shown to induce many IL-12 (interleukin 12)-responsive genes in common with STAT4α, in addition to a unique subset of genes [14].…”
mentioning
confidence: 94%